Subtractive and Additive Technologies in Fixed Dental Restoration: A Systematic Review - Rafal Kareem Rasheed; Nidhal Sahib Mansoor; Nihad Hasan Mohammed; Syed Saad B Qasim (Journal of Techniques)
Today, computers and digital devices are an indispensable part of our daily lives, and dentistry is no exception. Dentistry has adopted a number of digital technologies, including CAD/CAM (computer-aided design and manufacturing) systems. The goal of the current study is to evaluate the current state of knowledge on dental alloy manufacturing using subtractive and additive techniques for metal ceramic restoration. On this topic, an electronic systematic review was conducted in various databases (Science Direct, PubMed, Web of Science, and Google Scholar searches), as well as a hand search of the scientific literature. Published work was collected, analyzed, and relevant articles were chosen for inclusion in this review from 2008 to 2021. The online databases were searched for articles published that appeared between 2008 and 2021, with no time or language constraints we grouped relevant search terms together, such as "Computer-Aided Design, CAD/CAM, dentistry, dental fabrication, restoration, additive manufacturing." We recognized publications individually and systematically screened titles, summaries, and complete texts of the obtained publications. The findings indicate that current knowledge is sufficient to recommend subtractive manufacturing for crowns and fixed dental restorations for routine clinical use, with improvements in each of the current metal-ceramic veneering materials and procedures. According to the review, several digital technologies, such as systems of computer aided design and aided manufacturing were used in different dental specialties. Application of CAD/CAM technology provided numerous benefits while posing few limitations.